Large-scale Livestock Grazing A Management Tool for Nature Conservation - Plachter, Harald; Hampicke, Ulrich; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
One of the main objectives of nature conservation in Europe is to protect valuable cultural landscapes characterized by a mixture of open habitats and hedges, trees and patchy woodland (semi-open landscapes).The development of these landscapes during the past decades has been characterized by an ongoing intensification of land use on the one hand, and an increasing number of former meadows and pastures becoming fallow as a result of changing economic conditions on the other hand. Since species adapted to open and semi-open landscapes contribute to biodiversity in Europe in a major way, this development is of great concern to nature conservation. In several countries largescale, nature-adapted pastoral systems have been recognized as one solution to this problem. These systems could offer an alternative to industrial livestock raising and keep a high biodiversity on the landscape level. Against the background of livestock diseases such as BSE and Foot and Mouth Disease and the efforts to reform the Common Agricultural Policy in the EU by changing the criteria for agricultural subsidies, these concepts gain particular significance.They could also represent an alternative to the established, costly habitat management tools.
Livestock Grazing and Nature Conservation Objectives in Europe -- Extensive Livestock Farming #x2013; an Alternative Form of Nature Conservation Management? -- The Areas of Investigation -- Method Development -- Microscale Effects -- Mesoscale Effects -- Effects on Landscape Level -- Implementation of Large-Scale Grazing -- Nature Conservation Accounting for Large-Scale Livestock Grazing.
Keywords: Environment; Geobiology; Geography; Applied ecology; Landscape ecology; Geoecology; Environmental geology; Environment; Geoecology/Natural Processes; Biogeosciences; Geography, general; Applied Ecology; Landscape Ecology; Electronic books